PERILAKU MEROKOK DI KALANGAN MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Kurniawan, Rendra; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research was conducted at the Faculty of Social and Political Science, University of Riau in order to obtain information on the effect of warning the dangers of smoking to changes in smoking behavior of students. Problems in this study were (1) How motif smoking behavior of students in the Faculty of Social and Political Sciences? (2) What are the perceptions of students in the Faculty of Social and Political Sciences billboard warning against smoking? (3) How much influence billboard warning of smoking on smoking behavior of students in the Faculty of Social and Political Sciences ?. The title of this research is